Soil as an inexhaustible and high-performance anode material for Li-ion batteries. Issue 87 (15th September 2015) - Hu, Xiaofei; Zhang, Kai; Cong, Liang; Cheng, Fangyi; Chen, Jun
Abstract : Soil as an inexhaustible natural material is for the first time used as a high-performance anode in 18650-type full batteries. Abstract : Herein, we demonstrate that by a simple treatment of heating and ball-milling, soil is endowed with a 77.2% degree of defects and acts as a high-performance anode material for soil/Li half cells and 18650-type LiNi0.915 Co0.075 Al0.1 O2 (NCA)/soil full batteries that displayed a high and stable capacity of 3200 mA h (corresponding to 176 W h kg −1 and 522 W h L −1 ) in the 200th cycle at a high current of 4 A.